Predictive and prognostic values of pretreatment functional imaging-based biomarkers in advanced-stage laryngeal cancer - Eskiizmir, Görkem; Yılmaz Ovalı, Gülgün; Aras, Feray; Cengiz Özyurt, Beyhan; Tarhan, Serdar (ENT Updates, 2018)
Objective: To determine the quantitative values of apparent diffusion coefficient (ADC), standardized uptake values (SUVmax, SUVmean), metabolic tumor volume (MTV), metabolic tumor volume indexes (MTImax, and MTImean) using diffusion weighted-MRI (DW-MRI) and positron emission tomography/computed tomography (PET/CT), and analyze the predictive and prognostic values of these biomarkers in a homogenous group of patients with advanced-stage laryngeal cancer. Methods: Patients with newly diagnosed advanced-stage laryngeal cancer who had both DW-MRI and 18F-FDG PET/CT before treatment, and who had curative cancer treatment (surgery ± adjuvant therapy or radio ± chemotherapy) between 2011 and 2015 were included in this study. All patients were followed up clinically and radiologically, if necessary every 3 months for the first 2 years, every 4–6 months for year 3, and then annually thereafter. Results: Thirty-eight patients were retrospectively analyzed. Our analysis demonstrated statistically significant differences when the pretreatment SUV and MTImean value were compared between patients with stages III and IV. Standardized uptake value was also a predictive factor for N-stage. Moreover, a statistically significant difference was determined when patients with and without perinodal involvement (PNI) were compared. Log rank analysis demonstrated that none of functional imaging-based biomarkers had a prognostic role for oncological outcomes. Conclusion: Our results demonstrated that pretreatment SUV and MTImean values were predictive factors for staging, N-stage and PNI. Indeed, functional imaging-based biomarkers are promising, novel, noninvasive techniques that may provide additional information about tumor characteristics, treatment selection and prognosis in the near future.